Requirement Model of School Attendance Monitoring System (SAMS) in Secondary Schools - Roszana, Mohd Amin (2010)
The focus of this study is to get a good requirement model for Student Attendance Monitoring Systems (SAMS) in secondary school. It is aimed at system designer who want to know how to design an efficient SAMS. Methodology was used for this study requirement modelling process. The methodology comprises four main phases. requirements elicitation, requirements analysis, requirements management and requirements verification. At the end of this study, a SAMS prototype were designed based on the requirement model. User acceptance testing was conducted to examine user's satisfaction.